Згасаюча традиція: про одну групу навершь ранньоскіфського часу - Фрунт, О.С. (Археологія і давня історія України, 2022)
З початку ХХ ст. дослідники звертали увагу на специфічну серію навершь скіфського часу з пласкими зображеннями птахів на циліндричних втулках. Аналіз археологічного контексту показав, що ці знахідки пов’язані з ритуальними комплексами. Стилістичні особливості і відмінна від ранніх типів навершь конструкція є відображенням нових тенденцій в культурі кочовиків півдня Східної Європи у другій—третій чвертях VI ст. до н. е. Since the beginning of the 20th century, researchers have paid attention to a series of the Scythian poletops with flat images of birds. These findings are one of the indicators of the assemblages of the second—third quarter of the 6th century BC. At the moment, there are 4 sites in Central and Eastern Europe with finds of pole-tops from this series. These are Ulskii, barrow 2 (1909) and barrow 10 (1982) in the Kuban region, Răscăieţii Noi, barrow 1 in the Lower Dniester region and Zashchita, barrow 1 in the Dnieper Forest-Steppe. Pole-tops with a flat reduced image of bird heads are found in the Kuban sites, which can be considered as ritual places or shrines. Zashchita, barrow 1 can probably also be considered as a ritual place. There were no burial pits in such mounds. Under the burial mounds there were wooden structures with tent-shaped roofs or wooden canopy, but there were no human burials. Excavations of recent decades have revealed that a pair of pole-tops were part of a wooden altar and were located at the entrance to the ritual place. Probably, such pole-tops, like other sacred objects and details of the horse bridle, were ordered in one of the workshops in the Transcaucasus, where the art was formed under the influence of Lydian tradition of jewelry and toreutics. This can explain the fact that the finds differ from the early group of the pole-tops with rattles and three-dimensional figures of animals. The finds from Ulskii, barrow 2 (1909) and barrow 10 (1982) dated based on a horse bridle to the middle of the 6th century BC. The artifacts from Zashchita, barrow 1 and Răscăieţii Noi barrow appear to be replicas. They can be dated to the second half of the 6th century BC. Thus, the series of tops with flat reduced images of birds of prey was formed in the Kuban region and, apparently, as a result of the contacts of local elites with the Transcaucasus and the influence of Lydian jewelry art and toreutics. The archaeological context of the finds proves their use outside the funeral rite but at the same time expresses a connection with the idea of sacrifice and sacralization of space. These objects mark the final stage of their use in the ritual of the Early Scythian Age. From the last quarter of the 6th century BC poletops as a cultural phenomenon also disappeared in the 5th century BC. Future research will have to show why the tradition of using these ritual attributes faded out and was “reinstated’ in the 4th century BC. In conclusion, it should be noted that the results allow us to make changes in the classification of the pole-tops.